2020
DOI: 10.1007/s11306-020-01728-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and analysis of the quality assurance (QA) and quality control (QC) practices of LC–MS based untargeted metabolomics practitioners

Abstract: The Metabolomics Quality Assurance and Quality Control Consortium (mQACC) evolved from the recognized need for a community-wide consensus on improving and systematizing quality assurance (QA) and quality control (QC) practices for untargeted metabolomics. As an initial step, members of the consortium and several non-members who used liquid chromatography-mass spectrometry (LC-MS) untargeted metabolomics were asked to voluntarily participate in a collaborative research project and took part by providing the QA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 54 publications
1
75
0
Order By: Relevance
“…The samples can be obtained by pooling aliquots of each original sample and then following the same sample preparation protocol of the biological samples. Proposed in 2006 for the first time for untargeted metabolomics studies in order to check for data quality [ 100 ], QC samples have been and are used in numerous studies and several publications have highlighted their importance in the metabolomics workflow [ 59 , 61 , 98 , 99 , 101 ]. Broadhurst et al have reported on the different kinds of QC samples, and their respective advantages and limitations [ 98 ].…”
Section: Toward Inter-operable and Reusable Metabolomics Data For Biomarker Discovery: From Appropriate Project Design And Sample Collectmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples can be obtained by pooling aliquots of each original sample and then following the same sample preparation protocol of the biological samples. Proposed in 2006 for the first time for untargeted metabolomics studies in order to check for data quality [ 100 ], QC samples have been and are used in numerous studies and several publications have highlighted their importance in the metabolomics workflow [ 59 , 61 , 98 , 99 , 101 ]. Broadhurst et al have reported on the different kinds of QC samples, and their respective advantages and limitations [ 98 ].…”
Section: Toward Inter-operable and Reusable Metabolomics Data For Biomarker Discovery: From Appropriate Project Design And Sample Collectmentioning
confidence: 99%
“…This case deals with cohorts ranging from 200 to 500 samples, depending on the kind of sample preparation protocols and instruments used. It is the simplest one because recommendations on how to standardize the different steps of the untargeted metabolomics workflow and quality management practices (from the experimental design of the study to the submission of data into public repositories) are available and have been the subject of many publications [ 30 , 57 59 , 61 , 62 , 98 , 99 , 105 , 109 113 ] (Table 2 ).…”
Section: Toward Inter-operable and Reusable Metabolomics Data For Biomarker Discovery: From Appropriate Project Design And Sample Collectmentioning
confidence: 99%
“…As of 2021, metabolomics is considered a mature discipline with more than two decades of advancements in analytical workflows, software tools, and biological information in different biological systems (e.g., in vitro cells, plants, bacteria, animals) [ 10 , 44 ]. In parallel, guidelines to ensure data reliability and reproducibility have been proposed by the Metabolomics Standards Initiative (MSI) and the metabolomics Quality Assurance and Quality Control Consortium (mQACC) [ 117 , 118 ]. The MEtabolomics standaRds Initiative in Toxicology (MERIT) was created in 2017 to describe practical guidelines and minimal reporting standards for regulators to interpret the quality of metabolomics data in the context of regulatory toxicology [ 119 ].…”
Section: Quality Management Systemmentioning
confidence: 99%
“…The mQACC began to address the lack of guidelines and nomenclature by collecting detailed information on QA and QC practices used by different laboratories using LC-MS-based untargeted analysis [ 117 ]. Pooled QC samples were identified as one of the most commonly applied quality measurements in untargeted LC-MS-based metabolomics studies [ 117 ].…”
Section: Quality Management Systemmentioning
confidence: 99%
See 1 more Smart Citation